Can shocks to the discount factor explain business cycle fluctuations in Bulgaria (1999-2018)? - Aleksandar Vasilev (National Accounting Review, 2020)
A stochastic discount factor is introduced into a real-business-cycle setup with a government sector. The model is calibrated to Bulgarian data for the period 1999-2018, which is after the introduction of the currency board arrangement. The quantitative importance of shocks to the discount factor is investigated for the propagation of cyclical fluctuations in Bulgaria. In particular, allowing for a stochastic discount factor in the setup improves the model fit vis-a-vis data by increasing variability of employment and wages. However, those improvements are at the cost of increasing the volatility of consumption and investment.
Keywords: 330; business cycles; stochastic discount factor; Bulgaria